2019
DOI: 10.3390/en12010166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Productivity and Economic Viability of Combined Food and Energy (CFE) Production System in Denmark

Abstract: Agro-ecosystems for integrated food, fodder, and biomass production can contribute to achieving European Union goals to increase renewable energy sources and reduce greenhouse gas emissions. The study objective was to evaluate the productivity and economic returns from a combined food and energy (CFE) system compared to sole winter wheat and sole short rotation woody crop (SRWC) production. Two excel-based models viz. Yield-SAFE and Farm-SAFE, were used to simulate agronomic productivity and economic assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Nonetheless, it is an untapped by-product that could provide an extra amount of biomass for the production of bio-commodities. From this point of view, its collection should in theory be as high as possible, in order to reduce the fixed energetic costs of collection, as also recently suggested, taking into account that the producing bioenergy from the straw may have lower impacts compared to that from the grain [25] and that combining food and energy systems may allow for a further reduction of the environmental impact and to mitigate the climate-related fluctuations of the agricultural production and commodity value [26].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is an untapped by-product that could provide an extra amount of biomass for the production of bio-commodities. From this point of view, its collection should in theory be as high as possible, in order to reduce the fixed energetic costs of collection, as also recently suggested, taking into account that the producing bioenergy from the straw may have lower impacts compared to that from the grain [25] and that combining food and energy systems may allow for a further reduction of the environmental impact and to mitigate the climate-related fluctuations of the agricultural production and commodity value [26].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of higher productivity in agroforestry systems has been reported in different studies. The LER of a combined food and energy (CFE) production system in Denmark ranged from 1.14-1.34 [17], indicating that crop and tree yields produced in agroforestry required 14-34% less land or fewer resources in terms of light, water, nutrients, compared to monoculture. This is a significant advantage and provides avenues for ecological intensification to produce more with fewer inputs.…”
Section: Agronomic Productivitymentioning
confidence: 99%
“…The forestry system had a much lower financial equivalent annual value of EUR 194 ha −1 yr −1 with grants. However, in a 20-year field study of combined food and energy production systems in Denmark, calculations on agronomic productivity, costs of production, and revenue flows showed that agroforestry systems had higher net present values compared to monocrops [17]. Further, sensitivity analysis was carried out with different discount rates between 0-10%, and agroforestry systems were most insensitive to the discount rate and provided a stable and consistent net present value [17].…”
Section: High Costs For Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop yield in a rotation is calculated as the average yield over a whole crop rotation. LER of IFNS is the summation of partial LERs of each individual crop and tree components in a given IFNS system [12,13] In order to assess the economic viability, gross margins were calculated as follows [14] (Equation ( 2)):…”
Section: Agronomic Productivity and Economic Viabilitymentioning
confidence: 99%